Promoting equitable achievement in STEM: lab report writing and online peer review. Issue 1 (2nd January 2022) - Culver, K. C.; Bowman, Nicholas A.; Youngerman, Ethan; Jang, Nayoung; Just, Craig L.
Abstract: Although effective technical communication is an important outcome of undergraduate education in STEM fields, limited process-based writing instruction occurs in these disciplines. This study employed an experimental design to examine the use of Calibrated Peer Review (CPR), an online peer review platform, to improve lab report writing in an environmental engineering course. Students who completed methods and discussion modules using CPR earned higher grades on the final lab report than students who completed abstract and introduction modules (which are generally less difficult to write) using CPR. CPR also had indirect effects on lab report grade that occurred via greater accuracy in assessing lab report quality. Moreover, CPR performance and lab report grades were almost entirely unrelated to student demographics, whereas exam grade was frequently much higher among students from dominant populations.